2022
DOI: 10.53790/aemr.v2i1.27
|View full text |Cite
|
Sign up to set email alerts
|

Role of Social Media Marketing on SMES Brand Awareness in Nigeria

Abstract: This study investigated the impact of social media marketing on the brand awareness of the Small and Medium Scale Enterprises (SMEs) in Nigeria. The study employed descriptive survey to collect qualitative data from 458 online shoppers/customers. The study relied heavily on descriptive statistics and inferential statistics of regression to analyze the data. It was revealed that social media marketing improves the organization brand awareness and organization performance. It was revealed that factors such as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It is the most recent web based digital advertising strategy that has grown in prevalence owing to the growth of social networking sites such as Facebook, LinkedIn, and others (Nguyen et al, 2023;. Advertisement on social networking platforms, also referred as social advertising, is a paid type of organized company marketing and a means of promoting companies at a lower cost (Wójcik, 2022;Nwali, & Ntegeeh, 2022). It evolved into a global advertising platform and a customer-centric communication system to elicit a positive reaction from targeted consumers (Sheiner et al, 2021).…”
Section: Social Advertisement and Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…It is the most recent web based digital advertising strategy that has grown in prevalence owing to the growth of social networking sites such as Facebook, LinkedIn, and others (Nguyen et al, 2023;. Advertisement on social networking platforms, also referred as social advertising, is a paid type of organized company marketing and a means of promoting companies at a lower cost (Wójcik, 2022;Nwali, & Ntegeeh, 2022). It evolved into a global advertising platform and a customer-centric communication system to elicit a positive reaction from targeted consumers (Sheiner et al, 2021).…”
Section: Social Advertisement and Mediamentioning
confidence: 99%
“…As a result of its widespread acceptance and appealing qualities, social media has evolved into a promotional channel that is available to everybody through the internet (Mallik et al, 2022), and the notion of social advertising has arisen as a novel promotional paradigm. Social advertising acts as a technique of attracting potential audience's attention by driving visitors to social networking sites through content (Nwali, & Ntegeeh, 2022;. It is the most recent web based digital advertising strategy that has grown in prevalence owing to the growth of social networking sites such as Facebook, LinkedIn, and others (Nguyen et al, 2023;.…”
Section: Social Advertisement and Mediamentioning
confidence: 99%
“…The statistics from JAMB revealed that candidates enrolment for universities total 4,618,911 between 2007 and 2010 while combined figure for polytechnics and colleges of education totals 865,906. Nwali (2013) added that only very few candidates seeking admission into the university would want to go to the Polytechnic and this is only after such candidates have tried unsuccessfully in gaining admission into the university or when the parents are not financially buoyant. Fabian (2016) as reported by the guardian newspaper observed that there has been negative preference by most Nigerian candidates for universities over polytechnics and colleges of education in Nigeria.…”
Section: Introductionmentioning
confidence: 99%